2016
DOI: 10.1099/mic.0.000212
|View full text |Cite
|
Sign up to set email alerts
|

Growth and physiology of Clostridium perfringens wild-type and ΔazoC knockout: an azo dye exposure study

Abstract: Clostridium perfringens, a strictly anaerobic micro-organism and inhabitant of the human intestine, has been shown to produce the azoreductase enzyme AzoC, an NAD(P)H-dependent flavin oxidoreductase. This enzyme reduces azo dyes to aromatic amines, which are carcinogenic in nature. A significant amount of work has been completed that focuses on the activity of this enzyme; however, few studies have been completed that focus on the physiology of azo dye reduction. Dye reduction studies coupled with C. perfringe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Wild-type S. oneidensis can convert CalFluor488, to a fluorescent cycloaddition product in approximately 5 hours when combined and sealed with the appropriate Cu, ligand, and alkyne source 52 . We began by emulsifying an aqueous reaction containing aerobically grown S. oneidensis at an OD 600 of 6 x 10 - 5 , calculated such that one in every 10 droplets was filled 53 , using the fluorinated oil and biosurfactant as the oil phase. However, we measured no distinguishable fluorescent signal after 24 hours under these conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Wild-type S. oneidensis can convert CalFluor488, to a fluorescent cycloaddition product in approximately 5 hours when combined and sealed with the appropriate Cu, ligand, and alkyne source 52 . We began by emulsifying an aqueous reaction containing aerobically grown S. oneidensis at an OD 600 of 6 x 10 - 5 , calculated such that one in every 10 droplets was filled 53 , using the fluorinated oil and biosurfactant as the oil phase. However, we measured no distinguishable fluorescent signal after 24 hours under these conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Lots of anaerobic bacteria (Bacteroides sp., Eubacterium sp., Clostridium sp) and facultatively anaerobic bacteria (Proteus vulgaris, Streptococcus faecalis) can discolore azodyes in anaerobic conditions by restoring azocondensation [20]. So, for the bleaching of a monoazodye in anaerobic conditions Morrison et al a strain Clostridium perfringens was used Sharma et al the discoloration of methyl red under anaerobic conditions report using Aeromonas jandaei strain SCS5 [21,22]. The reactive violet 5 was discolored under anaerobic conditions using Bacterial mixed culture-SB4, say [23].…”
Section: Aerobic and Anaerobic Methodsmentioning
confidence: 99%
“…Studies by Morrison et al indicated that despite the existence of this system in Clostridium perfringens, Azo dyes such as tartrazine, Methyl Red, Trypan Blue, Direct Blue, and Methyl Orange slow down the growth of bacteria suggesting that there is a resistance to azo dyes in Clostridium perfringens. Therefore, there is a theory that different types of azoreductase may participate in the reduction of xenobiotics [29]. Studies by Rafii and coworkers confirmed that every single azoreductase-producing microorganism in the gut generates its own specific isoenzymes which might show different activities from others [30].…”
Section: Azoreducatsementioning
confidence: 99%